Transfer dynamics of macroplastics in estuaries – New insights from the Seine estuary: Part 3. What fate for macroplastics?. (August 2021) - Tramoy, R.; Gasperi, J.; Colasse, L.; Noûs, C.; Tassin, B.
Abstract: Macroplastic emissions from the Seine estuary to the English Channel were estimated using institutional cleaning of riverbanks, combined with a tagged litter experiment. Cleaning were performed between March 2018 and April 2019 by the non-profit company Naturaul'un over 19 sites covering 20 km of riverbanks. A total of 365 tagged litter (90% macroplastics) was released in the estuary in March ( n  = 200), at the end of the winter/spring flood 2018, in July ( n  = 58), August ( n  = 56) and September 2018 ( n  = 51) during low river flow periods. Over the total tagged litter, 102 (28%) were recovered by Naturaul'un . Relative to the total amount of macroplastics (>5 cm) collected and the estimated amount of smaller/hidden macroplastics (>5 mm) not collected, the maximum macroplastic emission to the English Channel was estimated to be ~100–200 metric tons per year. Graphical abstract: Unlabelled Image Highlights: Institutional cleaning on riverbanks in the Seine estuary are conducted since 2008. A tagged litter experiment was conducted to quantify macroplastic emissions. 28% of the tagged litter were recovered by institutional cleaning in one year. 100–200 mt/yr (maximum) of macroplastics are emitted to the sea. Cleaning on riverbanks are the best curative solutions to prevent plastics at sea.